The Finansial Inklusi Pada Peternak Sapi Pola Gaduhan Sebagai Penguatan Modal Sosial Dan Modal Finansial - Nur Solikin; Linawati Linawati; Samari Samari (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2021)
The existence of resources and production factors is an important component of supporting the business. Aspects of social capital and the availability of money, for cattle farmers are important parts, because cattle breeders must prepare forage forage needs, additional feed and fortifying feed (bran, concentrate) as a means of supporting the success of the livestock business being run. Financial inclusion in this study is defined as easy access to money. The “gaduhan” system (keeping other people's livestock) is often found in all corners of the village, livestock owners other than as animal providers often act as providers of money when people who raise livestock need (borrow) money. Social capital is built because of emotional closeness and financial capital is formed because of a joint effort to system gaduhan cattle. The purpose of the study was to analyze the application of financial inclusion to rowdy cattle farmers in strengthening social capital and financial capital. This type of research is descriptive qualitative by using questionnaires, interviews, FGD instruments to obtain primary data, secondary data sourced from relevant documents, articles. The subjects of the study were rowdy cattle breeders in the Semen District as many as 120 respondents. The results of the study indicate that the implementation of financial inclusion of the cattle rancher model has long been carried out between animal owners and animal keepers. Mutualism symbiosis is realized by mutually benefiting from raising cattle, strengthening social relations and economic income for both parties. Keywords: Financial inclusion, beef cattle breeders, gaduhan system